Perceiving and responding to gradual landscape change at the community level: insights from a case study on agricultural abandonment in the Black Forest, Germany - Bieling, Claudia (2013)
Abstract: How is gradual landscape change perceived and dealt with at the community level? Based on a case study approach, this question is investigated with regards to agricultural abandonment and the subsequent expansion of forests in the Black Forest, Germany. In the case presented, local residents’ perception of incremental landscape change does not correspond with a survey on biophysical features of landscape change, but rather focuses on visible effects and exhibits considerable time lags. Facing the same problem, local responses to change in two similarly structured and almost adjacent communities contrast strongly in character and outcomes. I conclude that local perceptions of change as well as specific community identities need to be taken into account in landscape management and policy. The promotion of specific examples of well-performing community-based management strategies, preferably by those people directly involved, should be considered as a particularly valuable dissemination tool